Dyarchy: democracy, autocracy and the scalar sovereignty of interwar India - Legg, Stephen (Duke University Press, 2016)
The 1919 Government of India Act instituted sweeping constitutional reforms that were inspired by the concept of “dyarchy”. This innovation in constitutional history devolved powers to the provinces and then divided these roles of government into reserved and transferred subjects, the latter of which would be administered by elected Indian ministers. Recent scholarship has been reassessing the local biopolitical potential unleashed by the 1919 Act. In this paper I revisit dyarchy at the national scale to show how this “All-India” re-visioning of Indian sovereignty was actually negotiated in relation to its imperial and international outsides and the exigencies of retaining governmental control inside the provinces. This paper will propose a constitutional historical geography of dyarchy, focusing on three scales and the forms of comparison they allow. First, Lionel Curtis’s political geometries and the international genealogies of his federalist aspirations are explored. Secondly, the partially democratic level of the province is shown to have been rigorously penetrated by, and categorically subordinated to, the central tier of colonial autocracy, which orchestrated a political geography of exclusion and exception. Finally, rival conceptions of time and sequentiality will be used to examine the basis for nationalist criticisms and exploitations of dyarchy’s reconfigurations of democracy, biopolitics, and the vital mass of the people.